Alpha2‐adrenoceptor agonists in small animal practice 2. Optimising clinical use. Issue 10 (15th November 2013) - Flaherty, Derek
Abstract : Alpha2 ‐adrenoceptor agonists are widely used for premedication, sedation and provision of analgesia in small animal practice. The first article in this series, which was published in the October issue of In Practice (vol 35, pp 524‐530), explained how the pharmacological properties of these agents result in both their desirable and less‐desirable effects. This article focuses on the most appropriate ways to use them practically to optimise their clinical benefits.